Drift-flux model for upward two-phase cross-flow in horizontal tube bundles. (May 2017) - Mao, Keyou; Hibiki, Takashi
Highlights: Literature review on void-fraction correlations of two-phase flow in tube bundles and available data for cross-flow in horizontal tube bundles has been performed. The criticality of the hydraulic diameter in a sub-channel of horizontal tube bundles has been addressed to distinguish the channel average and gap average mass velocity. Development methodology of the newly drift-flux correlation for upward two-phase cross-flow horizontal tube bundles has been performed. Comparison of the newly drift-flux correlation with experimental data as well as the error analysis have been presented. A full range drift-flux correlation has been developed based on interpolation scheme. Abstract: In relation to void fraction prediction of cross-flow in horizontal tube bundle of shell-tube heat exchangers, a drift-flux correlation has been developed to meet the demand on the study of two-phase flow gas and liquid velocities, two-phase pressure drop, heat transfer, flow patterns and flow induced vibrations in the shell side. Two critical parameters such as distribution parameter and drift velocity have been modeled. The distribution parameter is obtained by constant asymptotic values and taking into account the differences in channel geometry. The drift velocity is modelled depending on the density ratio and the non-dimensional viscosity number. The relationship between the channel averaged and gap mass velocity has been discussed in order to obtain the superficial gas and liquid velocities in the drift-flux correlation. The newly developed drift-flux correlation agrees well with cross-flow experimental databases of air-water, R-11 and R-113 in parallel triangular, normal square and normal triangular arrays with the mean absolute error of 1.06% and the standard deviation of 4.47%. In comparison with other existing correlations, the newly developed drift-flux correlation is superior to other studies due to the improved accuracy. In order to extend the applicability of the newly developed drift-flux correlation to void fraction of unity, an interpolation scheme has been developed. The newly developed drift-flux correlation is able to calculate the void fraction of cross-flow over a full range with different sub-channel configurations in shell-tube type heat exchangers.